2021
DOI: 10.1002/pri.1909
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross cultural adaptation, and construct validation of the Arabic version of the Frenchay Activities Index in people with multiple sclerosis

Abstract: Background and Purpose Assessing functional status in people with multiple sclerosis (PwMS) has a major role in determining how to help patients to reach their optimal level of living independently in the community. The Frenchay Activity Index (FAI) is a commonly used scale to evaluate functional status in rehabilitation research and practice settings. The aim of this study was to translate the FAI into the standard Arabic language through the process of cross‐cultural adaptation and to explore the internal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…[9,10,37] This indicates the strong reliability of the translated Arabic versions of KPPS and KPPQ, which will allow for a wider use of this tool and promote further studies for pain in PD in Arabic countries. The original English version of KPPS was recently translated to Arabic by a team from Jordan, [38] but our study also translated and validated the KPPQ along with KPPS and demonstrated comprehensively pain characteristics in Egyptian people with PD.…”
Section: Discussionmentioning
confidence: 82%
“…[9,10,37] This indicates the strong reliability of the translated Arabic versions of KPPS and KPPQ, which will allow for a wider use of this tool and promote further studies for pain in PD in Arabic countries. The original English version of KPPS was recently translated to Arabic by a team from Jordan, [38] but our study also translated and validated the KPPQ along with KPPS and demonstrated comprehensively pain characteristics in Egyptian people with PD.…”
Section: Discussionmentioning
confidence: 82%